PENGARUH ONLINE CUSTOMER REVIEW DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN SEPATU VENTELA - Gimnastiar, Gilang Nur (Media Mahardhika, 2024)
This study investigates the influence of online customer reviews and price perceptions on purchasing decisions in the post-pandemic Indonesian fashion industry, where electronic word-of-mouth (EWOM) has gained prominence, particularly through spontaneous customer reviews on social media platforms. These reviews, along with price perceptions, serve as crucial factors for consumers when making purchasing decisions. The research focuses on the partial influence of online customer reviews and price perceptions on purchasing decisions, employing a quantitative descriptive method. The population consists of students from Singaperbangsa University, Karawang, with a sample size of 96 respondents selected using the Slovin formula. Primary data was collected through online questionnaires distributed via Google Forms. Data analysis was conducted using SPSS version 25, and multiple linear regression testing yielded the equation Y = 6.050 + 0.343X1 + 0.382X2 + e. The findings show that price perception has the greatest impact on purchasing decisions. Additionally, a T-test revealed that online customer reviews (T = 2.801) and price perception (T = 3.895) both have a partial and significant influence on purchasing decisions, as their T values exceed the critical T value of 1.661.